Preparation method and application of two-dimensional CoS-CN nanosheet catalyst
By using ZIF-67 template to prepare two-dimensional CoS-CN nanosheet catalysts in the field of electrocatalytic water decomposition, the scarcity and stability of existing catalysts are solved, efficient and stable electrocatalytic water decomposition is achieved, and the electrolytic water is reduced. The energy consumption and cost of hydrogen production improve catalytic activity and electrical conductivity.
Patent Information
- Application Number
- CN202411333211.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-24
- Publication Date
- 2025-01-17
AI Technical Summary
Existing electrocatalytic water decomposition catalysts such as platinum-based materials and iridium dioxide have limited their large-scale application due to scarcity, high cost and stability issues, and the catalytic activity of transition metal sulfides in complex preparation processes and insufficient conductivity leads to their improvements in their catalytic activity. Restricted.
By using ZIF-67 as a template, combining solvent-thermal reaction and high-temperature pyrolysis steps, a two-dimensional CoS-CN nanosheet catalyst was prepared, and Co-CN powder was vulcanized under an inert atmosphere to form a two-dimensional carbon-supported metal with high efficiency catalytic activity. Sulfide composite material.
It realizes efficient and stable electrocatalytic water decomposition, reduces the energy consumption and cost of electrolyzed hydrogen production, provides economical and practical solutions, and optimizes catalytic activity by regulating the microstructure of nanosheets, significantly improving electrocatalytic efficiency.
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of catalyst preparation, and particularly relates to a preparation method of a two-dimensional CoS-CN nanosheet catalyst and application thereof. Background Art
[0002] The problem of global climate change is becoming increasingly serious, and reducing greenhouse gas emissions is urgent. The large-scale combustion of fossil fuels is the main source of greenhouse gas emissions, so the development of alternative energy sources has become the key. Hydrogen energy is regarded as an important part of the future energy system due to its advantages such as high energy density, easy storage and zero carbon emissions. Among the many hydrogen production technologies, electrocatalytic water decomposition has shown broad application prospects due to its green and environmentally friendly characteristics. However, the slow kinetics of the anode oxygen evolution reaction (OER) affects the efficiency of the cathode hydrogen evolution reaction (HER), and the high overpotential needs to be overcome, resulting in energy loss, which limits the efficiency and sustainable development of water electrolysis hydrogen production. At present, platinum (Pt)-based materials and iridium dioxide (IrO2) are considered to be the best catalysts for HER and OER, but their scarcity, high cost and stability issues limit their large-scale application. Therefore, the development of efficient, stable and inexpensive non-precious metal catalysts is of great practical significance.
[0003] Transition metal sulfides (TMSs), such as MoS2, WS2, CoS, NiS2, MnS, etc., as emerging non-precious metal electrocatalysts, have shown great potential in the field of electrocatalytic water splitting. Compared with precious metal catalysts, TMSs have the advantages of abundant reserves on the earth and low cost, and are expected to significantly reduce the cost of hydrogen production by electrolysis of water. The unique structural properties of TMSs enable the d-orbital electrons of transition metals to react with reactants (such as H + or H2O), thereby promoting the reaction. The metal-sulfur bond in TMSs has a moderate hydrogen adsorption free energy, and its polarization properties contribute to the adsorption and conversion of OER intermediates. Therefore, TMSs can achieve high HER and OER activities at a certain overpotential and reach a large current density. However, TMSs currently face the problems of complex preparation process, poor conductivity and insufficient stability in strong acid or strong base environments, which limit the further improvement of its catalytic activity and its wide application.
[0004] Therefore, how to further optimize the physicochemical properties of TMSs through reasonable material design and advanced synthesis methods and develop more efficient and stable electrocatalytic water decomposition materials is a difficult problem in current research. Summary of the invention
[0005] In order to overcome the above-mentioned shortcomings and deficiencies of the prior art, the primary purpose of the present invention is to provide a method for preparing a two-dimensional CoS-CN nanosheet catalyst.
[0006] The present invention uses ZIF-67 as a template, combines solvothermal reaction and high-temperature pyrolysis steps, and prepares a carbon-supported metal sulfide composite material (CoS-CN) with a two-dimensional sheet structure. This preparation method is not only efficient and environmentally friendly, but also can effectively reduce the cost of water electrolysis technology, providing an economical and practical solution to promote the large-scale promotion of this technology.
[0007] Another object of the present invention is to provide a two-dimensional CoS-CN nanosheet catalyst prepared by the above method.
[0008] Another object of the present invention is to provide an application of the above-mentioned two-dimensional CoS-CN nanosheet catalyst in the field of hydrogen production by water electrolysis, aiming to improve the efficiency and economy of hydrogen production by water electrolysis.
[0009] The purpose of the present invention is achieved through the following solutions: A method for preparing a two-dimensional CoS-CN nanosheet catalyst comprises the following steps: (1) Preparation of ZIF-67: Dissolve cobalt salt and 2-methylimidazole separately, mix, allow to react, and separate to obtain dimethylimidazole cobalt (ZIF-67) crystals; (2) Preparation of two-dimensional Co-ZIF nanosheets: Disperse ZIF-67 in a solvent, add cobalt salt, mix well, perform hydrothermal reaction, separate, and dry to obtain a solid product Co-ZIF; (3) Preparation of Co-CN nanosheets: Co-ZIF was pyrolyzed in an inert atmosphere to obtain Co-CN powder; (4) Preparation of CoS-CN nanosheets: Co-CN powder was sulfurized with thiourea in an inert atmosphere to obtain CoS-CN nanosheets.
[0010] The solvent used in each step of the preparation method is at least one of water and alcohol solvents.
[0011] The cobalt salt in step (1) and step (2) includes at least one of (CH3COO)2Co·6H2O, Co(NO3)2·6H2O, and CoCl2·6H2O.
[0012] The concentration of the cobalt salt solution after dissolution in step (1) is 0.05-0.5 mol / L; the concentration of the 2-methylimidazole solution is 0.05-4 mol / L.
[0013] The molar ratio of cobalt ions to 2-methylimidazole in the cobalt salt of step (1) is 1:(1-8).
[0014] The temperature of the static reaction in step (1) is room temperature and the time is 20-48 hours.
[0015] The separation in step (1) is centrifugal separation.
[0016] In step (2), the dosage ratio of ZIF-67, cobalt salt and solvent is 50-500 mg: 0.05-0.5 mol: 1 L.
[0017] The hydrothermal reaction temperature in step (2) is 100-150° C. and the reaction time is 4-24 hours.
[0018] The inert atmosphere in step (3) and step (4) includes at least one of nitrogen, argon and helium.
[0019] The heating rate of the pyrolysis in step (3) is 1-20°C / min, the pyrolysis temperature is 400-600°C, and the constant temperature holding time of the pyrolysis is 1-10h.
[0020] The sulfurization in step (4) is specifically to place the Co-CN powder in a tubular furnace, and place thiourea (as a sulfur source) at the ventilation upstream of the tubular furnace, and perform a sulfurization reaction under an inert atmosphere.
[0021] In step (4), the mass ratio of the Co-CN powder to thiourea is 1:(1-10).
[0022] The vulcanization heating rate in step (4) is 1-20°C / min, the temperature is 200-400°C, and the constant temperature holding time is 1-10h.
[0023] Two-dimensional CoS-CN nanosheet catalyst prepared by the above method.
[0024] Application of the above two-dimensional CoS-CN nanosheet catalyst in the field of hydrogen production by water electrolysis.
[0025] Compared with the prior art, the present invention has the following advantages and beneficial effects: (1) The preparation method of the two-dimensional CoS-CN nanosheet catalyst provided by the present invention does not rely on rare or toxic raw materials, significantly reduces production costs and reduces environmental impact, thereby achieving a more economical and environmentally friendly production and use process.
[0026] (2) The two-dimensional sheet structure of the two-dimensional CoS-CN catalyst prepared by the present invention gives it a larger electrochemical active area, which can expose more active sites, thereby maximizing contact with the electrolyte and promoting the adsorption and conversion of reactants. The present invention can effectively regulate the microstructure of the nanosheet by adjusting the pyrolysis temperature, thereby optimizing the catalytic activity of the material and reducing the energy consumption required for water electrolysis.
[0027] (3) The CN nanosheet structure of the catalyst prepared by the present invention has good conductivity, which can promote the rapid transmission of electrons on the catalyst surface and effectively reduce the resistance of charge transfer during the reaction. The composite structure of CoS and CN can form an effective electron transmission channel, accelerate the reaction kinetics, thereby improving the electrocatalytic efficiency and reducing the overpotential required for water electrolysis. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 This is the scanning electron microscope (SEM) image of ZIF-67.
[0029] Figure 2 This is the scanning electron microscope (SEM) image of Co-ZIF.
[0030] Figure 3 ac is the SEM image of the two-dimensional CoS-CN nanosheets obtained in Examples 1-3, and ac corresponds to Examples 1-3 respectively.
[0031] Figure 4 The X-ray diffraction (XRD) pattern of the two-dimensional CoS-CN nanosheets obtained in Examples 1-3.
[0032] Figure 5 This is the linear sweep voltammetry test diagram of the catalyst.
[0033] Figure 6 This is the catalytic stability test diagram of CoS-CN-600.
[0034] Figure 7 This is the AC impedance test diagram of the catalyst. DETAILED DESCRIPTION
[0035] The present invention is further described in detail below in conjunction with the examples and drawings, but the embodiments of the present invention are not limited thereto. If specific conditions are not specified in the examples, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.
[0036] Unless otherwise specified, the reagents used in the examples can be purchased from the market.
[0037] Example 1 (1) Preparation of ZIF-67 Cobalt nitrate hexahydrate (4 mmol) and 2-methylimidazole (4 mmol) were added to a 150 mL round-bottom flask, and 75 mL of methanol was added to disperse and dissolve them. Under stirring conditions, the 2-methylimidazole methanol solution was added to the cobalt nitrate hexahydrate methanol solution, mixed evenly, and then allowed to react for 24 hours. After the reaction was completed, ZIF-67 crystals were separated using a high-speed centrifuge.
[0038] (2) Preparation of two-dimensional Co-ZIF nanosheets Take 20 mg of ZIF-67 and disperse it in 50 ml of methanol solution, add cobalt nitrate hexahydrate (5 mmol), and disperse it evenly by ultrasound. Transfer the mixture to a high-pressure reactor, place it in a constant temperature electric heating blast drying oven, heat it to 120 ° C and keep it for 8 hours. After the reaction is completed, cool it naturally to room temperature, and filter and separate to obtain Co-ZIF.
[0039] (3) Preparation of Co-CN-400 nanosheets The Co-ZIF was transferred to a quartz boat and placed in a tube furnace. Under a nitrogen atmosphere, it was heated to 400°C at a heating rate of 5°C / min and kept at a constant temperature for calcination for 2 hours. After the calcination, it was cooled to room temperature to obtain Co-CN-400 powder.
[0040] (4) Preparation of CoS-CN-400 nanosheets 20 mg of Co-CN-400 powder was placed in a quartz boat and placed in a tube furnace. At the same time, 50 mg of thiourea (as a sulfur source) was placed in another quartz boat and placed upstream of the tube furnace. In a nitrogen atmosphere, the boat was heated to 300 °C at a heating rate of 5 °C / min and kept at a constant temperature for 2 hours for sulfurization treatment. After the reaction was completed, the boat was cooled to room temperature to obtain CoS-CN-400 nanosheets.
[0041] The application of the two-dimensional CoS-CN nanosheet catalyst obtained in this example in the electrolysis of water to produce hydrogen is as follows: (1) Preparation of working electrode: Place 5 mg of catalyst in a centrifuge tube, add 230 μL of deionized water, 230 μL of anhydrous ethanol and 40 μL of Nafion solution. Ultrasonic dispersion for more than 30 min to obtain a uniform catalyst ink. Take 100 μL of the ink and drip it twice on a 1 cm 2 The catalyst working electrode was prepared after drying, and the catalyst loading was 1 mg / cm 2 .
[0042] (2) Electrochemical performance test: All electrochemical performance tests were performed at room temperature using a Chenhua CHI 660e electrochemical workstation. The test used a three-electrode system, with a mercuric oxide electrode as the reference electrode, a platinum sheet as the counter electrode, a catalyst-loaded carbon cloth as the working electrode, and a 1M KOH solution as the electrolyte.
[0043] In the HER test, the CoS-CN-400 catalyst of this example exhibited excellent catalytic activity. 2 The required overpotential is 285mV.
[0044] Example 2 The difference from Example 1 is that the conditions of step (3) and step (4) are changed, and the specific conditions are adjusted as follows: (3) Preparation of Co-CN-500 nanosheets The Co-ZIF was transferred to a quartz boat and placed in a tube furnace. Under a nitrogen atmosphere, it was heated to 500°C at a heating rate of 5°C / min and kept at a constant temperature for calcination for 2 hours. After the calcination, it was cooled to room temperature to obtain Co-CN-500 powder.
[0045] (4) Preparation of CoS-CN-500 nanosheets 20 mg of Co-CN-500 powder was placed in a quartz boat and placed in a tube furnace. At the same time, 50 mg of thiourea (as a sulfur source) was placed in another quartz boat and placed upstream of the tube furnace. In a nitrogen atmosphere, the boat was heated to 400 °C at a heating rate of 5 °C / min and kept at a constant temperature for 2 hours for sulfurization treatment. After the reaction was completed, the boat was cooled to room temperature to obtain CoS-CN-500 nanosheets.
[0046] In the HER test, the CoS-CN-500 catalyst of this example exhibited excellent catalytic activity. 2 The required overpotential is 236mV.
[0047] Example 3 The difference from Example 1 is that the conditions of step (3) and step (4) are changed, and the specific conditions are adjusted as follows: (3) Preparation of Co-CN-600 nanosheets The Co-ZIF was transferred to a quartz boat and placed in a tube furnace. Under a nitrogen atmosphere, it was heated to 600°C at a heating rate of 5°C / min and kept at a constant temperature for calcination for 2 hours. After the calcination, it was cooled to room temperature to obtain Co-CN-600 powder.
[0048] (4) Preparation of CoS-CN-600 nanosheets 20 mg of Co-CN-600 powder was placed in a quartz boat and placed in a tube furnace. At the same time, 50 mg of thiourea (as a sulfur source) was placed in another quartz boat and placed upstream of the tube furnace. In a nitrogen atmosphere, the boat was heated to 400 °C at a heating rate of 5 °C / min and kept at a constant temperature for 2 hours for sulfurization treatment. After the reaction was completed, the boat was cooled to room temperature to obtain CoS-CN-600 nanosheets.
[0049] In the HER test, the CoS-CN-600 catalyst of this example exhibited excellent catalytic activity. 2 The required overpotential is 147mV.
[0050] Comparative Example 1 The difference from Example 3 is that the hydrothermal reaction in step (2) is omitted, and the CoS@CN material with a three-dimensional structure is prepared directly from ZIF-67. The specific steps of this example are as follows: (1) Preparation of ZIF-67 Cobalt nitrate hexahydrate (4 mmol) and 2-methylimidazole (4 mmol) were added to a 150 mL round-bottom flask, and 75 mL of methanol was added to disperse and dissolve them. Under stirring conditions, the 2-methylimidazole methanol solution was added to the cobalt nitrate hexahydrate methanol solution, mixed evenly, and then allowed to react for 24 hours. After the reaction was completed, ZIF-67 crystals were separated using a high-speed centrifuge.
[0051] (2) Preparation of Co@CN 50 mg of ZIF-67 was heated to 600 °C at a heating rate of 5 °C / min under a nitrogen atmosphere and calcined at a constant temperature for 2 hours. After calcination, it was naturally cooled to room temperature to obtain a black sample powder Co@CN.
[0052] (3) Preparation of CoS@CN 50 mg of Co@CN powder was placed in a quartz boat and placed in a tube furnace. At the same time, 50 mg of thiourea (as a sulfur source) was placed in another quartz boat and placed upstream of the tube furnace. In a nitrogen atmosphere, the boat was heated to 400°C at a heating rate of 5°C / min and kept at a constant temperature for 2 hours for sulfurization treatment. After the reaction was completed, the boat was cooled to room temperature to obtain a three-dimensional CoS@CN material.
[0053] In the HER test, the CoS@CN catalyst in this example reached a current density of 10 mA / cm 2 When the overpotential is 379 mV, it is higher than the two-dimensional sheet-structured CoS-CN catalyst prepared in Example 3. This may be because the electrochemical active area of the three-dimensional CoS@CN material is smaller and the number of exposed active sites is reduced, resulting in its catalytic activity being lower than that of the two-dimensional sheet-structured CoS-CN catalyst.
[0054] Comparative Example 2 The difference from Example 1 is that this example uses a strong acid (aqua regia) to remove the transition metal Co component, thereby preparing a CN nanosheet material with a two-dimensional structure. The specific steps are as follows: (1) Preparation of ZIF-67 Cobalt nitrate hexahydrate (4 mmol) and 2-methylimidazole (4 mmol) were added to a 150 mL round-bottom flask, and 75 mL of methanol was added to disperse and dissolve them. Under stirring conditions, the 2-methylimidazole methanol solution was added to the cobalt nitrate hexahydrate methanol solution, mixed evenly, and then allowed to react for 24 hours. After the reaction was completed, ZIF-67 crystals were separated using a high-speed centrifuge.
[0055] (2) Preparation of two-dimensional Co-ZIF nanosheets Take 20 mg of ZIF-67 and disperse it in 50 ml of methanol solution, add cobalt nitrate hexahydrate (5 mmol), and disperse it evenly by ultrasound. Transfer the mixture to a high-pressure reactor, place it in a constant temperature electric heating blast drying oven, heat it to 120 ° C and keep it for 8 hours. After the reaction is completed, cool it naturally to room temperature, and filter and separate to obtain Co-ZIF.
[0056] (3) Preparation of Co-CN-400 nanosheets The Co-ZIF was transferred to a quartz boat and placed in a tube furnace. Under a nitrogen atmosphere, it was heated to 400°C at a heating rate of 5°C / min and kept at a constant temperature for calcination for 2 hours. After the calcination, it was cooled to room temperature to obtain Co-CN-400 powder.
[0057] (4) Preparation of CN nanosheets 20 mg of Co-CN-400 powder was added to a glass container containing 50 mL of aqua regia and soaked at room temperature for 5 h to remove Co. After treatment, the solid was separated using a high-speed centrifuge and washed three times with an ethanol-water mixture (volume ratio 1:1) and dried to obtain CN nanosheets.
[0058] In the HER test, the CN catalyst in this example reached a current density of 10 mA / cm 2 When the overpotential is 475 mV, it is significantly higher than the overpotential of the CoS-CN catalyst in the previous example. This shows that the introduction of the CoS component can effectively improve the HER catalytic activity of the material. The catalytic activity of the CN nanosheet material may come from its own defective structure or nitrogen atom doping.
[0059] Analysis of attached pictures: from Figure 1 From the SEM image of ZIF-67 in the figure, it can be seen that the synthesized ZIF-67 is a regular rhombic dodecahedron with a particle size of about 500-900 nm.
[0060] from Figure 2 From the SEM image of Co-ZIF in, it can be seen that ZIF-67 is converted into Co-ZIF through solvothermal reaction, and the morphology changes from a regular rhombic dodecahedron to a two-dimensional sheet structure.
[0061] Figure 3 The SEM images of CoS-CN prepared at different pyrolysis temperatures are shown. It can be observed that the obtained CoS-CN all present a two-dimensional nanosheet structure, and CoS particles are clearly distributed on the surface of the nanosheet. This two-dimensional sheet structure can significantly increase the specific surface area of the catalyst, forming highly exposed active sites, thereby enhancing the accessibility of the electrolyte and improving the catalytic performance.
[0062] like Figure 4 In the X-ray diffraction (XRD) patterns shown, CoS-CN-400, CoS-CN-500 and CoS-CN-600 samples show diffraction peaks at 28.5°, 32.3°, 36.3°, 46.3° and 55.0°, corresponding to the (200), (210), (220) and (311) crystal planes of cobalt sulfide, respectively. This indicates that these diffraction peaks completely match the standard diffraction peaks of cobalt sulfide, confirming the presence of cobalt sulfide in the material.
[0063] Figure 5 The linear sweep voltammetry (LSV) curve of the material is shown. As can be seen from the figure, the CoS-CN-600 material exhibits the best hydrogen evolution reaction (HER) catalytic performance. When the current density is 10mA / cm 2 When the overpotential is 147 mV, CoS-CN-600 requires only 147 mV. In contrast, CoS-CN-500 and CoS-CN-400 require overpotentials of 236 mV and 285 mV, respectively. In the comparative example, CoS@CN and CN require overpotentials of 379 mV and 475 mV, respectively.
[0064] Figure 6 The LSV curve comparison of CoS-CN-600 catalyst before and after 1000 cyclic voltammetry (CV) tests is shown to evaluate the stability of the catalyst. As can be seen from the figure, after 1000 cyclic voltammetry tests, the performance of CoS-CN-600 remained stable with a current density of 10mA / cm 2 When the overpotential increases by only 20 mV, it demonstrates its excellent stability and durability in practical applications.
[0065] Figure 7 The AC impedance spectra show that the charge transfer resistances of CoS-CN-400, CoS-CN-500, and CoS-CN-600 are 11.5Ω, 9.2Ω, and 5.6Ω, respectively. CoS-CN-600 exhibits the lowest charge transfer resistance, and thus has the fastest electron transfer rate and optimal reaction kinetics.
[0066] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.
Claims
1. A method for preparing a two-dimensional CoS-CN nanosheet catalyst, characterized in that: The following steps are involved: (1) Preparation of ZIF-67: Dissolve cobalt salt and 2-methylimidazole separately, mix, allow to react, and separate to obtain ZIF-67 crystals; (2) Preparation of two-dimensional Co-ZIF nanosheets: Disperse ZIF-67 in a solvent, add cobalt salt, mix well, perform hydrothermal reaction, separate, and dry to obtain a solid product Co-ZIF; (3) Preparation of Co-CN nanosheets: Co-ZIF was pyrolyzed in an inert atmosphere to obtain Co-CN powder; (4) Preparation of CoS-CN nanosheets: Co-CN powder was sulfurized with thiourea in an inert atmosphere to obtain CoS-CN nanosheets.
2. The method for preparing the two-dimensional CoS-CN nanosheet catalyst according to claim 1, characterized in that: The cobalt salt in step (1) and step (2) includes at least one of (CH3COO)2Co·6H2O, Co(NO3)2·6H2O, and CoCl2·6H2O; The concentration of the cobalt salt solution after dissolution in step (1) is 0.05-0.5 mol / L; the concentration of the 2-methylimidazole solution is 0.05-4 mol / L.
3. The method for preparing the two-dimensional CoS-CN nanosheet catalyst according to claim 1, characterized in that: The molar ratio of cobalt ions to 2-methylimidazole in the cobalt salt of step (1) is 1:(1-8); The temperature of the static reaction in step (1) is room temperature and the time is 20-48 hours.
4. The method for preparing the two-dimensional CoS-CN nanosheet catalyst according to claim 1, characterized in that: In step (2), the dosage ratio of ZIF-67, cobalt salt and solvent is 50-500 mg: 0.05-0.5 mol: 1 L; The hydrothermal reaction temperature in step (2) is 100-150° C. and the reaction time is 4-24 hours.
5. The method for preparing the two-dimensional CoS-CN nanosheet catalyst according to claim 1, characterized in that: The inert atmosphere in step (3) and step (4) includes at least one of nitrogen, argon and helium.
6. The method for preparing the two-dimensional CoS-CN nanosheet catalyst according to claim 1, characterized in that: The heating rate of the pyrolysis in step (3) is 1-20°C / min, the pyrolysis temperature is 400-600°C, and the constant temperature holding time of the pyrolysis is 1-10h.
7. The method for preparing the two-dimensional CoS-CN nanosheet catalyst according to claim 1, characterized in that: In step (4), the mass ratio of the Co-CN powder to thiourea is 1:(1-10).
8. The method for preparing the two-dimensional CoS-CN nanosheet catalyst according to claim 1, characterized in that: The vulcanization temperature rise rate in step (4) is 1-20°C / min, the temperature is 200-400°C, and the constant temperature holding time is 1-10h.
9. A two-dimensional CoS-CN nanosheet catalyst prepared by the method according to any one of claims 1 to 8.
10. Application of the two-dimensional CoS-CN nanosheet catalyst according to claim 9 in the field of hydrogen production by water electrolysis.